Clinical, Microbiological, and Biochemical Outcomes of Hyaluronic Acid in Non-Surgical Periodontal Therapy: A Systematic Review and Meta-Analysis - Alessia Pardo; Veronica Magnani; Pietro Montagna; Andrea Ala; Gabriele Brancato; Federica Melloni; Giorgio Lombardo; Daniele De Santis (Applied Sciences)
Aim: This systematic review and meta-analysis evaluated the adjunctive use of hyaluronic acid (HA) in non-surgical periodontal therapy to improve clinical outcomes in patients with moderate-to-severe chronic periodontitis. The aim was to assess its effectiveness in reducing probing pocket depth (PPD), improving clinical attachment level (CAL), and decreasing bleeding on probing (BOP). Methods: Four electronic databases were searched (PubMed, Cochrane Library, Scopus, Web of Science, Grey Literature) for randomized controlled trials (RCTs) published until January 2025 and involving otherwise healthy patients treated with scaling and root planing (SRP) plus HA after at least 12 weeks of follow-up. Risk of bias was assessed using RoB 2.0; data were collected on clinical assessment, microbiological, and biochemical analysis and then analyzed using a fixed-effects or random-effects model considering the high heterogeneity of the included studies, which calls for caution when interpreting the results. Results: Fourteen of the 21 RCTs reviewed underwent a meta-analysis. Compared with SRP alone, the addition of adjunctive HA ≥ 0.8% led to an improvement in PPD, but the reduction in BOP was less consistent. Biochemical markers indicated less inflammation, oxidative stress, and selective antimicrobial activity. Although studies on 0.2% HA are still limited, improvements have been observed in clinical parameters, along with better biochemical and microbiological outcomes in the experimental group compared to the control group. Conclusions: Despite moderate heterogeneity and methodological limitations, the evidence supports the use of HA combined with SRP in periodontal treatment.